Low-level copy number changes of MYC genes have a prognostic impact in medulloblastoma - Zitterbart, Karel; Filkova, Hana; Tomasikova, Lenka; Necesalova, Eva; Zambo, Iva; Kantorova, Dagmar; Slamova, Iva; Vranova, Vladimira; Zezulkova, Dita; Pesakova, Martina; Pavelka, Zdenek; Veselska, Renata; et al. (Journal of neuro-oncology, 2011)
High-level amplifications of MYC genes are associated with poor outcomes in childhood medulloblastoma (MB). However, the occurrence of MYCN and MYCC copy number increases below the intense amplification pattern is rarely reported, and its clinical impact has not yet been determined. Here, we describe this phenomenon and its prognostic significance in a cohort of 29 MB patients. Using interphase fluorescence in situ hybridization (I-FISH), low-level copy number alterations, i.e. gain of MYCN, were shown in 5/27 (19%) samples, whereas amplification was revealed in only 1/27 (4%) samples. MYCC gain was revealed in 6/29 (21%) MB, while amplification was disclosed in only 2/29 (7%). Hyperploidy and co-incidence of gains in both MYC loci were frequently observed in samples with copy number aberrations. Survival analysis has clearly shown that MYC copy number increases are associated with lowered event-free survival and overall survival in MB. In the case of MYCN, this negative correlation was statistically significant. We conclude that limited numerical alterations in loci 2p24 (MYCN) and 8q24 (MYCC), as assessed by I-FISH, are present in MB with a higher frequency than high-level amplifications. Poor prognoses were observed in patients with copy number increases in MYC genes. Our data illustrate the importance of further investigations in multicenter trials to better refine the emerging genomic-based prognostic stratification in MB.
Keywords: protoonkogenní proteiny c-myc; Humans; protoonkogen n-myc; Interphase; dítě; kohortové studie; In Situ Hybridization, Fluorescence; Child; N-Myc Proto-Oncogene Protein; interfáze; Female; Medulloblastoma; Proto-Oncogene Proteins c-myc; genová dávka; amplifikace genu; jaderné proteiny; lidé; meduloblastom; Cohort Studies; předškolní dítě; Survival Rate; Cerebellar Neoplasms; ženské pohlaví; Gene Amplification; Male; hybridizace in situ fluorescenční; Retrospective Studies; Adolescent; prognóza; Nuclear Proteins; nádory mozečku; onkogenní proteiny; Prognosis; retrospektivní studie; míra přežití; mužské pohlaví; prospektivní studie; Child, Preschool; Gene Dosage; mladiství; Oncogene Proteins; Prospective Studies